Analisis Keputusan Calon Nasabah Memilih Produk Asuransi Prucinta di PT Prudential Life Assurance Binjai - Yusrizal Yusrizal; Sonia Ritonga (Masyarakat Ekonomi Syariah Bogor, 2022)
The decision of a prospective customer to choose a product is a decision-making process that begins with the introduction of needs from various options then evaluates them and decides on a choice of a product from many choices.So the decision of a prospective customer in choosing a product is a process that is carried out by a prospective customer when choosing the product, then the prospective customer chooses one of the products from the existing product choices. so that there are no good obstacles that the decisions taken can have effects and cause problems in other fields so that when making decisions, one must be careful in life assurance at the Binjai branch, including products, prices, locations and places where people promote Prucinta products to achieve sales targets for agents or marketers will carry out the prospect of a product presentation fact-finding approach and closing or closing Keywords : prospective customer decisions, the importance of decisions, prucinta products